Strategies in anti-adhesion therapy: A review article - Fitua Al-Saedi (College of Pharmacy / Mustansiriyah University, 2022)
Bacterial diseases are an important cause of mortality and morbidity worldwide. The Improper and uncontrolled use of antibiotics contribute to the bacterial resistance to antibiotics. It is well known that the antibiotics stop bacterial infections by killing or   inhibiting their growth. Antibiotics are interfering with critical functions that are important for bacterial growth. To overcome this, bacteria developed different mechanisms to resist the antibiotics and survive.  Targeting bacterial function without killing them is a promising way to inhibit bacterial infection. Bacterial adherence is a serious step towards infection. Anti -adhesion therapy aims to inhibit bacterial infection via interfering with bacterial attachment without killing them. This review will cover different strategies in anti-adhesion therapy.